2005
DOI: 10.1111/j.1445-2197.2005.03315.x
|View full text |Cite
|
Sign up to set email alerts
|

Modified saphenous−peritoneal shunt in refractory ascites: new technique

Abstract: This modified procedure not only improved the nutritional status of cirrhotic patients with refractory ascites but also improved their quality of life. Infections and obstructions decreased in the short term. However, long-term follow up is mandatory. This new technique requires more practice and experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…It had been reported that DIC and other complications such as volume overload may be prevented by evacuating ascites before the insertion of the shunt [85] . Additionally, these complications have not been reported in the most recent studies using saphenoperitoneal shunts [82][83][84] . These results should be interpreted, nevertheless, cautiously because most studies did not indicate the MELD or Child Pugh scores of their study population.…”
Section: Article In Pressmentioning
confidence: 95%
See 2 more Smart Citations
“…It had been reported that DIC and other complications such as volume overload may be prevented by evacuating ascites before the insertion of the shunt [85] . Additionally, these complications have not been reported in the most recent studies using saphenoperitoneal shunts [82][83][84] . These results should be interpreted, nevertheless, cautiously because most studies did not indicate the MELD or Child Pugh scores of their study population.…”
Section: Article In Pressmentioning
confidence: 95%
“…Fourteen studies [72][73][74][75][76][77][78][79][80][81][82][83][84][85] reported the outcome of patients with PVS. Baseline characteristics are found in Supp.…”
Section: Pvsmentioning
confidence: 99%
See 1 more Smart Citation